Management of vital teeth discoloration with in-office bleaching techniques using hydrogen peroxide 40%: A case report - Sari, Ermita; Dwiandhany, Wahyuni S. (Journal of Case Reports in Dental Medicine, 2022)
Objective: This case report aims to describe the treatment of discolored vital teeth with in-office bleaching using 40% hydrogen peroxide.Method: A 41-year-old woman visits the Dental Hospital of Hasanuddin University and complained of yellow teeth in the last five years. The patient has a habit of consuming black tea. The teeth were treated with in-office bleaching techniques with procedures cleaning the tooth surface using a brush and prophylactic paste, then determining the teeth' color using the Opalescent Boost shade guide. Retract the lips using of cheek retractor (Optra gate). The teeth to be bleached are dried and followed by the application of an astringent agent (Acteon Expasyl). Application of gingival barrier (Opaldam Ultradent) to protect the gingiva. Application of bleaching agent H2O2 (Opalescent Boost Ultradent) for 20 minutes. Clean the bleaching material then determine the color of the teeth after bleaching. Apply desensitizing agent (UltraEz Ultradent). Remove the gingival barrier and give instructions after bleaching to the patient.Result: The treatment showed an increase in the brightness of tooth color. The patient showed no complaints of gingival irritation and tooth sensitivity. Extraoral and intraoral examinations showed no abnormalities.Conclusion: In-office bleaching techniques are a minimally invasive treatment for discolored vital teeth that can provide satisfactory esthetic results.